Optimisation of the CT pulmonary angiogram (CTPA) protocol using a low kV technique combined with high iterative reconstruction (IR): A phantom study. Issue 2 (March 2023) - Bellizzi, A.; Bezzina, P.; Zarb, F.
Abstract: Introduction: This study aims to optimise the current CTPA protocol at a public general hospital in Malta using lower kV combined with high Iterative Reconstruction (IR) (>50%). Methods: The research consisted of a 2-phase anthropomorphic phantom study. Phase 1: radiation dose evaluation of 6 experimental protocols consisting of the low kV technique and high IR values and comparison with the current protocol. Phase 2: image evaluation. Objective image quality was evaluated in terms of contrast to noise ratio (CNR) and signal to noise ratio (SNR). Subjective image quality evaluation was performed by 3 radiologists undertaking Absolute Visual Grading Analysis (VGA). Resultant image quality scores were analysed using Visual Grading Characteristics (VGC). Results: All experimental protocols achieved significant (p < 0.05) dose reductions. SNR and CNR improved in almost all protocols, however, differences were not significant (p > 0.05). In subjective image quality analysis, the current protocol provided significant superior image quality (AUC > 0.5; p < 0.05) when compared to the experimental protocols consisting of 80 kV with 70%, 80%, 90% and 100% IR. The only two experimental protocols yielding comparable image quality to the current protocol were 80 kV with 50% IR (AUC: 0.195; p: 0.137) and 80 kV with 60% IR (AUC: 0.554; p: 0.624). The protocol yielding the greatest decrease in radiation dose being 80 kV with 60% IR. Conclusions: The optimal IR value was 60%. When applying the optimal experimental protocol (80 kV combined with 60% IR), a significant dose reduction was achieved while maintaining diagnostic image quality. Implications for practice: The low kV technique combined with high IR parameter is easily implemented and involves no additional cost and equipment.